Operational Stress Injuries and the Mental Health and Well‐Being of Veteran Spouses: A Scoping Review. Issue 3 (25th May 2018) - Norris, Deborah; Eichler, Maya; Cramm, Heidi; Tam‐Seto, Linna; Smith‐Evans, Kimberley
Abstract: This article presents the results of a scoping review of literature focusing on the relationship between operational stress injuries (OSIs) in military veterans and spousal mental health and well‐being. Using elements of the family adjustment and adaptation response (FAAR) model as an organizing framework, the research reviewed focuses on the demands the OSIs place on the family system, as well as related capabilities and meanings, and how these demands have an impact on the spouse and the marital relationship.